Unconfined Compressive Strength and Damage Evolution in Geopolymer-Stabilized Clay Shale: Role of Temperature and Alkali Activator Ratio - Willis Diana; Edi Hartono; Agus Setyo Muntohar; Nurza Purwa Abiyoga (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
Exposed clay shale is highly susceptible to weathering and rapid strength degradation, which often leads to slope and earth-structure instability. Geopolymer-based soil stabilization has emerged as a promising method to improve the mechanical properties of such problematic materials. However, this chemical stabilization process is sensitive to environmental conditions, particularly temperature fluctuations. The performance of geopolymer-stabilized clay shale under elevated-temperature conditions remains insufficiently investigated, particularly in tropical regions such as Indonesia, where temperatures can fluctuate between 25◦C and 40◦C, and the exposed ground surface may reach up to 60◦C during the dry season because of intense solar radiation. This study evaluates the effectiveness of fly ash–based geopolymer in stabilizing clay shale under temperature variations ranging from 26◦C to 60◦C. A series of laboratory experiments was conducted using two alkali activator ratios (Na2SiO3:NaOH), namely 2.0 (Ratio A) and 2.5 (Ratio B). Mechanical performance was assessed through unconfined compressive strength (UCS) tests, stress–strain analysis, and energy-based damage evolution to quantify strength development and failure behavior. The results indicate that temperature is the dominant factor controlling strength development. A 10◦C increase in curing temperature resulted in a 40–60% increase in UCS, whereas variations in the alkali activator ratio produced only a 15–20% increase. The highest strength amplification, reaching 16 times that of untreated soil, was achieved using Ratio B at 60◦C, while Ratio A showed strength stagnation above 50◦C. Microstructural observations suggest that elevated temperatures accelerate geopolymer gel formation, leading to higher initial stiffness and an expanded elastic region. However, this also resulted in more brittle behavior, characterized by a higher brittleness index and rapid post-peak damage propagation for Ratio B, whereas Ratio A exhibited greater ductility. Overall, higher curing temperatures increased the dissipated energy at failure and revealed a clear strength–ductility trade-off. These findings provide insights for optimizing geopolymer stabilization of clay shale, particularly for geotechnical applications in tropical environments where elevated in situ temperatures are common.